(untitled) (Revista LIDER, 2020)
This paper analyzes from the socio-intercultural point of view the juxtaposition of the Yoreme ethno region many dimensions of the information rhetoric, at least three of them describe not only the asymmetries, but the asynchronies that, when considering time, are present between the reality of the people of Yoreme Mayo of Sinaloa and global aspirations. These dimensions are: 1) the linguistic rights of indigenous communities in the new context of acceptance of ethnic and cultural diversity, 2) promotion of new policies on access to public information, and 3) the global aspirations of forming a society of information and knowledge with the use of New Technologies of Information and Communication (NTICs). It is proposed in this paper that the interaction of these three dimensions results in a large gap with the objectives set by the major national and global organizations that have placed stakes on the intercultural future of humanity and the information society.